Philosophical Chronicles - Nancy, Jean-Luc (Book collections on Project MUSE., 2008)
"In eleven brief, engaging talks originally broadcast on French public radio, Jean-Luc Nancy offers a philosopher's account of some of the pressing questions of our day and addresses chronic issues within philosophical inquiry. The fundamental question is whether philosophy is conditioned by the world the philosopher inhabits, or whether it must remain unconditioned by that world. The essays amount to the vision to a philosopher sensitive to the world and attempting to open his path within it."--Jacket.